Realisation of Czech vowels in reading of Francophone speakers - Polachova, Pavla (Bohemica Olomucensia, 2023)
The present study focuses on the acoustic analysis of spoken Czech of Francophone speak- ers and focuses on the realization of vowels (which were measured and evaluated using the Praat program). The background material for the analysis were audio-recordings of loud Czech reading by 50 students studying Czech with French as a mother tongue. The analysis shows that the realization of Czech vowels is influenced by negative transfer from the native language, which decreases with higher language level.
Keywords: Czech as a foreign language; Pronunciation; Phonetic analysis; Czech vowels; French vowels